Inbreeding in cattle populations under natural service, artificial insemination and embryo transfer - Silva, Roberto Gomes da (Pesquisa Agropecuaria Brasileira, 2014)
Three methods of reproduction (natural breeding, artificial insemination, and embryo transfer) were compared with respect to their effects upon the inbreeding coefficient of a hypothetical 200.000 cattle population, ten successive generations along, under the following assumptions: no mutation, 100% of fertility and 100% of calving, constant effective population number, random mating, variable number of offspring per sire and per dam, sire and dam replacement rate of 50% per generation, constant environmental variance, anf full additive genetic variance. The results indicated that under the conditions of the used model, natural breeding affects the inbreeding coefficient f only if the population is subdivided into isolates; artificial insemination and embryo transfer cause increases of about 0.3% and 2.5% per generation respectively in the value of f. The frequency of recessive homozygotes increases in the absence of selection, but decreases rapidly if selection is carried against them, both under artificial insemination and embryo transfer. Under natural service, genetic variance of quantitative characters In the over-all population increases slightly, but decreases rapidly under artificial insemination and embryo transfer, this effect boing more pronounced as higher is the value of heritability.